Differences between the combination of the 25-gauge vitrectomy with phacoemulsification versus 20-gauge vitrectomy and phacofragmentation - Romero-Aroca, Pere (Dove Medical Press, 2009)
INTRODUCTION: In the present study we determine the differences observed between 25-gauge-vitrectomy combined with phacoemulsification, and the 20-gauge-vitrectomy combined with pars plana phacofragmentation. METHODS: A prospective study of a sample of 987 eyes of 661 patients randomly divided into two groups. 25-gauge-vitrectomy plus phacoemulsification included 486 eyes, and 20-gauge-vitrectomy plus phacofragmentation 501 eyes. We evaluated the differences at the time of the surgery, the intra-and postoperative complications, and the variations in intraocular pressure. RESULTS: The final visual outcome was similar in both groups. The most important differences between groups were: surgical time was faster in group 1 than in group 2, (mean time: 35.16 ± 3.49, 44.74 ± 5.30 minutes). Intraoperative complications were more numerous in group 1. In group 1, postoperative low levels of intraocular pressure are present in all patients with 2.77% of patients with hypotension (<8 mmHg), and three choroidal effusion. In group 2, intraocular lens decentration and retinal detachment are more frequent (2.38% and 1.39%, respectively). CONCLUSIONS: In the present study, both techniques have a similar number of complications and have a similar postoperative outcome, and are valid for the management of the pathologies selected.